La prise en compte du vieillissement dans les écoquartiers : l’exemple de la participation autour de la résidence intergénérationnelle de Saint-Cyprien (Poitiers) - Nicolas D’Andréa; Florence Zérillo (Développement Durable et Territoires)
Neither towns nor rural areas are well adapted to a multi-generational society. Is sustainable urbanism capable of meeting this challenge, in particular by encouraging elderly participation ? The french scientific literature and calls for bids for Eco-neighbourhood projects from the Environment Ministry show only a passing interest in the question of ageing. Locally, however, the sensitivity regarding this question as well as existing partnerships can combine with eco-neighbourhood dynamics to produce an innovative approach inspired by new forms of cohousing. The participative support involving the renovation of social housing in an intergenerational home in Poitiers is an example of this. While the project may seem difficult to replicate, it should be feasible as long as community work is placed at the heart of the approach and not just the idea of a new standard.